2003
DOI: 10.1207/s15327914nc4601_09
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of DMBA-Induced Mouse Skin Tumor Development by Inositol Hexaphosphate and Its Mode of Action

Abstract: Inositol hexaphosphate (IP6) or phytic acid, contained in most mammalian cells, has been shown to have anticancer and anti-cell-proliferative effects in several experimental models of carcinogenesis. We investigated the effect of topical application of IP6 on 7,12-dimethylbenzanthracene (DMBA)-induced complete carcinogenesis and on selective critical events of proliferation, differentiation, or apoptosis after DMBA exposure. IP6 inhibited skin tumor development significantly in a dose-dependent manner. IP6 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…25) Also some studies seem to demonstrate a capacity of InsP 6 to inhibit skin cancer. 26,27) In the present paper a first study of the absorption of InsP 6 through the skin is developed. .…”
Section: -5)mentioning
confidence: 99%
See 1 more Smart Citation
“…25) Also some studies seem to demonstrate a capacity of InsP 6 to inhibit skin cancer. 26,27) In the present paper a first study of the absorption of InsP 6 through the skin is developed. .…”
Section: -5)mentioning
confidence: 99%
“…26,27) In the present paper a first study of the absorption of InsP 6 through the skin is developed.…”
mentioning
confidence: 99%
“…On the other hand, at least two protons are bound to IP anion at pH above 12. The low log K [7][8][9][10][11][12] (pKa [1][2][3][4][5][6] ) values of PO 3 2-group of IP listed in Table 1 indicate that protons dissociate very easily from subsequent phosphate groups.…”
Section: Resultsmentioning
confidence: 99%
“…The in vivo as well as in vitro studies have shown that phytic acid is an important antioxidant and the presence of IP in living cells has beneficial effects such as protection against cancer, heart diseases, diabetes and renal calculosis [6][7][8]. Anticancer and biological activity of this compounds is related to the IP interaction with nucleic acids [9][10][11][12], RNA editing enzyme [13] and kinase [14]. Moreover, phytic acid can be used as corrosion inhibitor, component of toothpaste, in dental cements and mouthwashes [4].…”
Section: Introductionmentioning
confidence: 99%
“…28 Moreover, IP-6 was able to inhibits DMBA-induced mouse skin and mammary tumor development. 23,27 The decreased level of NO following IP-6 administration may be explained by its antioxidant activity. In support, intrinsic IP-6 in corn and soy was protective against lipid peroxidation in colon of pigs.…”
Section: Discussionmentioning
confidence: 99%